The Definitive Guide to JSF in Java EE 8 Building Web Applications with JavaServer Faces - Scholtz, Bauke (Apress, 2018)
Learn and master the new features in the JSF 2.3 MVC web framework in this definitive guide written by two of the JavaServer Faces (JSF) specification leads. The authors take you through real-world examples that demonstrate how these new features are used with other APIs in Java EE 8. You'll see the new and exciting ways JSF applications can use to communicate between a client and a server, such as using WebSockets, invoking bean methods directly from Ajax, executing client-side JavaScript when Ajax calls complete, and more Along the way you'll broaden your knowledge of JSF components and web APIs best practices, and learn a great deal about the internals of JSF and the design decisions that have been made when building the JSF API. For example, you'll see what artefacts are now CDI injectable, how CDI changed JSF internally, and what some of the caveats are when working with the CDI versions of a JSF artefact. Furthermore, you'll build an example application from scratch. After reading The Definitive Guide to JSF in Java EE 8, you'll be ready to build your own efficient and secure web applications. You will: Leverage the new features in JSF 2.3 in your existing applications Integrate JSF and CDI Use the brand new Component Search Expression framework, which enables you to more easily locate components from your template Extend the Component Search Expression framework with your own search operators Work with the different ways of mapping requests to JSF, make your application use extensionless URLs, and programmatically inspect which resources are present in your application Master the best practices for web application development and see which are obsolete.